O deserto nas cartas de São Jerônimo - Leite, Eduardo Silva (2021)
Our work focuses on how the idea of desert is presented in the letters of St. Jerome. We used the epistolary published by the Library of Christian Authors, with introduction, version, and notes by Daniel Ruiz Bueno, a bilingual edition from 1962. We focus on the Christianization of late Roman society, especially the 4th century. Christianity gradually introduced itself into social groups, especially in the Roman aristocracy, having as a fundamental element its ability to dialogue from its intellectuals with properly Roman formation. Based on this assumption, Jerome is an example of such a capacity for dialogue. Roman Christian — formed in the classic molds of his time — makes constant use of epistolary forms of communication, modulating with classic tops recognized by the target social group, in order to promote not only Christianity, but also his name as a Christian ascetic champion. We also present the relevance of the desert, which constitutes the power that the ascetic scholarly discourse imposed on ancient Roman society. In this sense St. Jerome explores the tops of the desert due to his intellectual and social project, which led us to the selection of 35 letters by which we could give proof of the use and configuration that the author gives to the desert, especially as regards the shapes, and manners to project the subjects to spiritual levels acceptable to the learned monk, a use resulting from the position of chancellor of Jerome's Christianity, who, realizing the value of the desert tops, did not hesitate to use it in the Christianization of the Roman elite of his time.